2001
DOI: 10.1071/aj00029
|View full text |Cite
|
Sign up to set email alerts
|

Geological Controls on Overpressure in the Northern Carnarvon Basin

Abstract: A small, but significant fraction of wells drilled in the Northern Carnarvon Basin have encountered problems with overpressure: better pore pressure prediction would improve safety and economy for drilling operations. In the Northern Carnarvon Basin the occurrence of overpressure and likely mechanisms are under investigation as part of the Australian Petroleum Cooperative Research Centre (APCRC) Research Program on Pore Pressure Prediction. Previous workers have proposed a number of mechanisms as the main caus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…Tingay et al (2007) demonstrated the likely vertical transfer of overpressure up normal faults within the inner shelf of the Baram Delta, Borneo. Other notable areas where such pressure transfer is documented include that of the Northern Carnarvon Basin, northwest Australia shelf (van Ruth et al, 2000;Dodds et al, 2001;Tingate et al, 2001;Hoskin et al, 2015), and the Qaidam Basin, northwest China (Fan et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Tingay et al (2007) demonstrated the likely vertical transfer of overpressure up normal faults within the inner shelf of the Baram Delta, Borneo. Other notable areas where such pressure transfer is documented include that of the Northern Carnarvon Basin, northwest Australia shelf (van Ruth et al, 2000;Dodds et al, 2001;Tingate et al, 2001;Hoskin et al, 2015), and the Qaidam Basin, northwest China (Fan et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Tingay et al (2007) demonstrated the likely vertical transfer of overpressure up normal faults within the inner shelf of the Baram Delta, Borneo. Other notable areas where such pressure transfer is documented is that of the Northern Carnarvon Basin, Northwest Australia Shelf (van Ruth et al, 2000;Dodds et al, 2001;Tingate et al, 2001;Hoskins et al, 2015) and the Qaidam Basin, northwest China (Fan et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The wells we have analysed in this paper are cited as being mainly affected by disequilibrium compaction (Nyein et al, 1977, Vear, 1998, Swarbrick and Hillis (1999, Tingate et al, 2001, van Ruth et al, 2004and Sagala and Tingay, 2012. The Barrow wells also have not had significant Tertiary re-burial (Tingate et al 2001). Swarbrick (2012).…”
Section: Discussionmentioning
confidence: 84%
“…The loading model in the Madeleine Trend and Kendrew Trough areas will not work in the Barrow sub-basin, where wells such as Barrow Deep-1 and Barrow L35J and F-24J are similarly uplifted (Dodds et al, 2001;Tingate et al 2001, van Ruth et al, 2004and Sagala and Tingay, 2012. These wells have been influenced by fluid expansion processes rather than purely disequilibrium compaction (Zaunbrecher, 1994, van Ruth et al, 2004and Sagala and Tingay, 2012.…”
Section: Discussionmentioning
confidence: 99%